Pengaruh Pengaruh ROA, DER, DPS terhadap Harga Saham di JII70 Periode 2018-2023 - Fahniati, Raden Ayu; Juwita, Ratna (MDP Student Conference, 2025)
This study aims to see the effect of ROA, DER, and DPS partially and simultaneously on stock prices in the Jakarta Islamic Index 70 period 2018-2023. The sample used in the study was 165 from 27 companies in a 6-year period. Partial research results show that Return On Asset and Debt to Equity Ratio have a negative and insignificant effect on Stock Prices. Dividend Per Share has a positive and significant effect on Stock Price. The results of the study simultaneously show that Return On Asset, Debt to Equity Ratio, and Dividend Per Share have a positive effect on Stock Prices.